Treatment of Early Allergic and Late Inflammatory Symptoms of Allergic Rhinitis with Petasites Hybridus Leaf Extract (Ze 339): Results of a Noninterventional Observational Study in Switzerland - Maren Blosa; Julia Uricher; Sabine Nebel; Catherine Zahner; Veronika Butterweck; Jürgen Drewe (MDPI AG, 2021)
The primary objective of this noninterventional, observational study was to assess the effectiveness of the Petasites hybridus leaf extract (Ze 339) on early allergic and late inflammatory symptoms of allergic rhinitis in Swiss outpatients. This study was conducted by general practitioners and allergologists. Data from 226 patients were collected during three documented visits. The intermediate visit was ideally made 2-4 weeks after the baseline visit, followed by the final visit approximately 2-4 months later. The mean study duration was 63 days, with 75% of patients being treated for at least 4 weeks. Of the patients, 58.5% started with Ze 339 monotherapy, and 41.5% received other antiallergic and/or sympathomimetic drugs. In both groups, the allergic total symptom score and the inflammatory total symptom scores were significantly (p < 0.001) reduced, and the scores for quality of life were improved. Both physicians and patients were very satisfied with the treatment and the concept of therapy, not only for short-term (seasonal) therapy but also for long-term therapy. The tolerability was good: only three mild gastrointestinal adverse events occurred. In summary, the effectiveness of P. hybridus leaf extract Ze 339 for the treatment of early allergic and late inflammatory symptoms of allergic rhinitis could be confirmed.